From cheder to jeshiva in Polish diaspora... – two-degree system of jewish religious schools and its contemporary transformations - Cukras-Stelągowska, Joanna (Paedagogia Christiana, 2009)
This paper shortly summerizes the history of jewish religious education in Poland – from the beginning in the XV century on the Polish lands, its growth during the XIX period, its domination between First and Second World War and finally total destruction in 1968. It took 28 years before it was possible to open a Jewish secular elementary school in Warsaw (1996), thanks to the assistance from the Ronald Lauder Foundation. Four years later, on initiative of Jews in Wrocław the Lauder Etz-Chaim elementary school was founded in this city. Democratization of social life in Poland after 1989 contributed to the change in Jews attitudes to their national descent. For many, their ‘Jewishness’, which now can be spoken about openly, has become the object of profound interest, intellectual search or the way to stress one’s individuality. As a result, we can also observe the process of rebuilding Jewish religious life and forming sunday’s schools, cheders and “Talmud academies” at Jewish Community in Warsaw, Krakow, Lodz, Gdansk and Wrocław (rather as a part of informal education, non- orthodox, more or less religious and adapted to modern jewish life-style in European diaspora).